KARAKTERISTIK KEGIATAN KEAGAMAAN DI SMK DHARMA WIDYA SEBAGAI IMPLEMENTASI PENDIDIKAN KARAKTER - Sabar Marjoko (Pascasarjana Universitas Hindu Indonesia, 2024)
This research aims to explore the value of the characteristics of Buddhist religious activities at Dharma Widya Vocational School as an implementation of student character education in Buddhist-based schools. This type of research is a case study which aims to explore a case by involving the collection of various sources of information. The characteristics of religious activities in Buddhist-based schools certainly differ from each other because they relate to the values that are to be built. There are several activities that are characteristic of religious activities at Dharma Widya Vocational School, such as silent sitting, pabbajja atthasilani, dhamma class, commemoration of Buddhist holidays, almsgiving and social service. These various activities are a form of implementing character education which is adapted to the Strengthening Character Education stipulated by the Ministry of Education and Culture, namely to shape students to have religious, nationalist, independent, mutual cooperation and integrity attitudes.